Implementasi kurikulum merdeka pada pembelajaran IPAS :Studi fenomenologi di SDN 101/II Muara Bungo - Nurhana, Siti; Aprizan, Aprizan; Subhanadri, Subhanadri; Wiyoko, Tri; Dani, Refril (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research is based on a lack of understanding by educators regarding the independent curriculum in science and science learning, a lack of integration in science and science learning, and a lack of training among fellow educators regarding the independent curriculum in science and science learning. This research aims to interpret the planning, implementation and assessment of science and science learning at SDN 101/II Muara Bungo. This research uses a qualitative and phenomenological approach; the research was carried out at SDN 101/II Muara Bungo. Participants in qualitative research with a phenomenological approach are Class IV and Class V teachers. The procedure for selecting participants in this research uses purposive sampling, interviews, observation, and documentation to carry out data collection techniques, and activities in data analysis are carried out by data collection, data reduction, data presentation. and conclusion. Data analysis was strengthened using the IT atlas application and triangulation as data validity. The results of this research show that: 1) science AS learning planning is designed by analysing the independent criteria platform, which contains learning outcomes, learning objectives, flow of learning objectives and open modules; 2) educators collaborate with colleagues to design science AS learning, 3) implementation Independent curriculum science and science learning is suitable for using the Think pair score (TPS) strategy and the Discovery Learning model, 4) assessment of science and science learning using diagnostic assessments (physical and psychological assessments), formative (games, quizzes, appreciation), summative (daily tests, UTS, UAS ).